Propulsion of copper microswimmers in folded fluid channels by bipolar electrochemistry. Issue 11 (19th January 2017) - Jiang, Jin-Zhi; Guo, Mei-Hong; Yao, Fen-Zeng; Li, Ju; Sun, Jian-Jun
Abstract : We report for the first time that conducting objects could be propelled in folded liquid filled channels by bipolar electrochemistry. Abstract : We report for the first time that conducting objects could be propelled in folded liquid filled channels by bipolar electrochemistry. This approach was based on controlling the formation of hydrogen bubbles at one extremity of a bipolar electrode. In this work, copper wires used as microswimmers could move in folded channels with angles from 30° to 180° by bubble propulsion and the velocity fluctuated over time. A proportional relation between polarization voltage and average velocity in linear channel was verified. The motion of microswimmers could be controlled within these types of channels in space and time, which might broaden the applications of micromachines in bipolar electrochemistry.